The Effect of Production of Selected Agriculture Products and Money Supply on GDP of Agriculture Sector in Malaysia - Devaki a/p, Kanaga Retnam (2012)
Agriculture sector plays the vital role in Malaysian economic because of the contribution of agriculture during the early stages of the national economic growth until now. The purpose of this paper is to examine the effects of the selected agriculture sector (palm oil, rubber, rice and saw logs) in the agriculture sector and to examine the impact of money supply across employment and productivity of labour and capital in agriculture sector. This paper uses the secondary data from year 1981 until 2010 from the Department of Statistics Malaysia, Malaysia Productivity Corporation (MPC) and Asian Development Bank (ADB). By using Johansen-Julies Cointegration model, the results showed there is long run relationship between dependent variable and independent variables. But, in Granger Causality model, result showed there is no relationship between money supply and productivity variables. While, this paper also conducts other tests such as Autocorrelation, Ramsey RESET and Histogram Normality Test.